(untitled) (Indonesian Journal of Civil Engineering Study, 2025)
Workplace accidents are occurrences that have an impact on workers who carry out construction activities. The level of risk that has an effect ranges from low to severe risk in every workplace accident in construction activities. Data collection was carried out on the implementation of the K3 program in the construction project of the STIE II Semarang campus. Data were obtained by distributing questionnaires to both workers and development implementers. Furthermore, the results of the analysis can be used to evaluate the implementation of the Occupational Health and Safety (OHS) program to minimize workplace accidents that may occur in the construction process. The research method used is to determine the ranking of each item of the assessment of the implementation of the OHS program which is then analyzed by the Mean value. Based on the results of the analysis, it was found that the obstacle that became an inhibiting factor in implementing the OHS program in his construction process was the minimum paradigm of workers regarding occupational safety and health. The workers consider that Personal Protective Equipment (PPE) is not a basic need at work. The workers feel uncomfortable using PPE when they are at the construction site. In addition, workers are used to working as is without self-protection.